2019
DOI: 10.1055/s-0037-1611721
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Aldol Additions of Glycolic Acid and Its Derivatives

Abstract: This review gives a comprehensive overview of aldol additions of glycolic acid derivatives to achiral aldehydes and acetals affording α,β-dihydroxycarboxylic acids or derivatives thereof. The focus is on simple diastereoselectivity. A selection of related aldol additions is also presented: aldol additions of glycolic acid derivatives to ketones with two different substituents and aldol additions of α-substituted glycolic acid derivatives.1 Introduction1.1 Organization of this Review1.2 Outside the Scope of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 174 publications
0
2
0
Order By: Relevance
“…Remarkably, the method tolerated the introduction of an oxygenated substituent at the Cα position of the acyl group (Eq 3 in Scheme 15 ). 34 35 As a result of a thorough scrutiny of the Cα alcohol protecting group, we found that α-pivaloyloxy thioimide 62 was particularly suitable for such a glycolate aldol reaction. As shown in Scheme 15 , dimethyl acetals of aromatic and α,β-unsaturated aldehydes reacted with the titanium enolate of 62 in the presence of BF 3 ·OEt 2 at –78 °C, whereas dialkyl acetals from aliphatic aldehydes, less likely to generate the necessary oxocarbenium intermediate, required SnCl 4 and a higher temperature (Scheme 15 ).…”
Section: Chiral-auxiliary-based Processesmentioning
confidence: 97%
“…Remarkably, the method tolerated the introduction of an oxygenated substituent at the Cα position of the acyl group (Eq 3 in Scheme 15 ). 34 35 As a result of a thorough scrutiny of the Cα alcohol protecting group, we found that α-pivaloyloxy thioimide 62 was particularly suitable for such a glycolate aldol reaction. As shown in Scheme 15 , dimethyl acetals of aromatic and α,β-unsaturated aldehydes reacted with the titanium enolate of 62 in the presence of BF 3 ·OEt 2 at –78 °C, whereas dialkyl acetals from aliphatic aldehydes, less likely to generate the necessary oxocarbenium intermediate, required SnCl 4 and a higher temperature (Scheme 15 ).…”
Section: Chiral-auxiliary-based Processesmentioning
confidence: 97%
“…Koreeda and Luengo applied a similar strategy in the pursuit of the formation of diastereomerically pure ( Z )- and ( E )-1-alkoxy-1,3-butadienes using a glycolate aldol addition strategy . This strategy was successful but was limited by low diastereoselectivities (d.r.…”
Section: Introductionmentioning
confidence: 99%